Sequevar Diversity and Virulence of Ralstonia solanacearum Phylotype I on Mayotte Island (Indian Ocean) - Chesneau, Thomas; Maignien, Géraldine; Boyer, Claudine; Chéron, Jean-Jacques; Roux-Cuvelier, Michel; Vanhuffel, Luc; Poussier, Stéphane; Prior, Philippe (Frontiers in Plant Science, 2018)
The genetic and phenotypic diversity of the Ralstonia solanacearum species complex, which causes bacterial wilt to Solanacae, was assessed in 140 strains sampled from the main vegetable production areas of the Mayotte island. Only phylotype I strains were identified in the five surveyed areas. The strains were distributed into the following 4 sequevars: I-31 (85.7%), I-18 (5.0%), I-15 (5.7%), and I-46 (3.6%). The central area of Mayotte was the most diverse region, harboring 4 sequevars representing 47.1% of the collected strains. Virulence tests were performed under field and controlled conditions on a set of 10 tomato breeding line accessions and two commercial hybrid tomato cultivars. The strains belonging to sequevar I-31 showed the highest virulence on the tomatoes (pathotypes T-2 and T-3), whereas sequevars I-18, I-15, and I-46 were grouped into the weakly T-1 pathotype. When the tomato accessions were challenged in the field and growth chambers, the highest level of resistance were observed from the genetically related accessions Hawaii 7996, R3034, TML46, and CLN1463. These accessions were considered moderately to highly resistant to representative strains of the most virulent and prevalent sequevar (I-31). Interestingly, the Platinum F1 cultivar, which was recently commercialized in Mayotte for bacterial wilt resistance, was highly or moderately resistant to all strains. This study represents the first step in the rationalization of resistance deployment strategies against bacterial wilt-causing strains in Mayotte.